The Coexistence of Genetic Mutations in Thyroid Carcinoma Predicts Histopathological Factors Associated With a Poor Prognosis: A Systematic Review and Network Meta-Analysis - Zhao, Ling; Wang, Lin; Jia, Xiaomeng; Hu, Xiaodong; Pang, Ping; Zhao, Sitong; Wang, Yajing; Wang, Jing; Zhang, Yingshi; Lyu, Zhaohui (Frontiers in Oncology, 2020)
Purpose: Genetic mutations may play an important role in the progression and invasion of thyroid carcinoma (TC), and their coexistence may result in mutational synergy. The presence of the BRAFV600E mutation, as well as mutations affecting the TERT promoter, RAS, CHEK2 and RET/PTC, may all have an impact on prognosis. The aim of this study was to explore whether synergy between the coexistent mutations predicts histopathological prognostic factors that influence disease outcome. Methods: A comprehensive literature search of PubMed, Embase and the Cochrane Library, from their inception until January 2020. Primary outcomes included: disease stage, lymph node metastasis, extrathyroidal extension and distant metastasis; while, secondary outcomes included: tumor recurrence, mortality, invasion of thyroid capsule, multiplicity, presented as an odds ratio (OR) with 95% credible intervals (CrI). Results: 27 publications (comprising 9 active intervention arms), involving 8388 TC patients, were selected. Network meta-analytic estimates of active interventions contrasted with other active interventions, with random effects, were calculated. In terms of outcomes focus on overall TC, BRAFV600E + TERT co-mutation ranked highest for diseases stage (OR=5.74, 95% CrI: 3.09-10.66), as well as lymph node metastasis, extrathyroidal extension (5.74, 4.06-8.10), tumor recurrence (7.21,3.59-14.47) and invasion of the thyroid capsule(3.11, 1.95-4.95). BRAFV600E + TERT co-mutation ranked secondary in distant metastasis, mortality and multiplicity, which ranked highest was TERT+RAS or RAS. When we were limited to the study of patients with papillary TC (PTC), BRAFV600E + TERT always ranked highest for primary outcomes: disease stage (6.39,3.13-13.04), lymph node metastasis, extrathyroidal extension (5.80,3.89-8.64) and distant metastasis (7.33, 3.00-17.89); while, BRAFV600E + TERT again ranked highest in secondary outcomes: tumor recurrence (7.23,3.37-15.51), mortality (9.26, 3.02-28.42), invasion of thyroid capsule (3.20,2.01-5.11) and multiplicity. Conclusions: In this molecular marker mutation-based systematic review and network meta-analysis, we found that coexistent BRAFV600E + TERT genetic co-mutations predicted poor histopathological prognosis, including progression, invasion, and metastasis, especially in PTC. For the overall TC, the BRAFV600E + TERT + RAS triple mutations may have a greater impact on the prognosis, and further research should related to potentially important features. This study is registered with PROSPERO, number CRD42019143242.